A quick and effective methodology for analyzing dinotefuran and its highly polar metabolites in plum using liquid chromatography-tandem mass spectrometry. (15th January 2018) - Rahman, Md. Musfiqur; Abd El-Aty, A.M.; Kabir, Md. Humayun; Chung, Hyung Suk; Lee, Han Sol; Hacımüftüoğlu, Fazil; Jeong, Ji Hoon; Chang, Byung-Joon; Shin, Ho-Chul; Shim, Jae-Han
Graphical abstract: Highlights: A simultaneous method was developed for dinotefuran and its highly polar metabolites in plum. Mass-up was introduced instead of salting out for exact quantitation. Internal standard is not needed for the newly developed methodology. The method can be used either as it is or with slight modification in other matrices. Abstract: A simple and effective method was developed for analyzing dinotefuran and its three metabolites (MNG, UF, and DN) in plum using liquid chromatography-tandem mass spectrometry (LC-MS/MS). Due to the polarity and high water miscibility, dinotefuran and some of its metabolites (especially DN) have some limitations to be extracted with acetonitrile and salt following the "QuEChERS" sample preparation methodology. Alternatively, the samples were extracted with methanol, and purified with dispersive-solid phase extraction procedure (d-SPE) using primary secondary amine (PSA) and C18 sorbents after filtration, and mass up. Due to the suppression effect originated from plum matrix, matrix-matched calibration curves, which provided good linearity with coefficient of determination ( R 2 ) ≥ 0.998, were used for quantification of all analytes. Blank plum samples fortified with 2 spiking levels (10 × LOQ and 50 × LOQ) yielded satisfactory recoveries for all tested analytes in the range of 83.01 to 110.18% with relative standard deviation (RSD) ≤ 8.91. The method was successfully applied to field-incurred plum samples and dinotefuran and all metabolites were positively detected and quantified. In conclusion, we suggest that the method can be expanded to polar compounds having solvent and partitioning problems in any of the versions of QuEChERS.